Thinking Skills of Junior High School Students Related to Gender - Arifin Riadi; Noor Laila Atini; Rolina Amriyanti Ferita (SAINTIS Publishing, 2019)
This study aims to determine the relationship between gender and students’ thinking skills and compare their score between male and female based on their level of thinking skills. Moreover, the result of this study can also be used to evaluate the implementation of the 2013 Curriculum on mathematics junior high school especially Higher-Order Thinking Skills. The method used in this study is ex-post facto, with a population of all 7th grade public junior high schools students in Banjarmasin city. Sample taken were 391 students, divided into 6 schools that were selected randomly. The instrument used is 16 multiple choice test that is valid and reliable. This developed test respectively focused on measuring thinking skills, namely Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating. The result showed that female students were better than male students in almost all of the thinking skills, except Creating. However, there is no relationship between gender and thinking skills.